2021
DOI: 10.3389/fenrg.2021.625188
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Valorization to Produce Porous Carbons: Applications in CO2 Capture and Biogas Upgrading to Biomethane—A Mini-Review

Abstract: Porous carbon materials, derived from biomass wastes and/or as by-products, are considered versatile, economical and environmentally sustainable. Recently, their high adsorption capacity has led to an increased interest in several environmental applications related to separation/purification both in liquid- and gas-phases. Specifically, their use in carbon dioxide (CO2) capture/sequestration has been a hot topic in the framework of gas adsorption applications. Cost effective biomass porous carbons with enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 61 publications
0
22
0
Order By: Relevance
“…At maximum engine load, 3 kg adsorbent adsorbs a maximum of 27% and 36% of CO 2 emissions than that by 0.75 kg adsorbent in the D100 and JME20 operations, respectively. This is mainly due to the excellent surface affinity and active pores in the palm shell‐based adsorbent 41–43 . Overall, it is found that palm shell‐based adsorbent exhibits significant CO 2 adsorption capacity in both operations.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…At maximum engine load, 3 kg adsorbent adsorbs a maximum of 27% and 36% of CO 2 emissions than that by 0.75 kg adsorbent in the D100 and JME20 operations, respectively. This is mainly due to the excellent surface affinity and active pores in the palm shell‐based adsorbent 41–43 . Overall, it is found that palm shell‐based adsorbent exhibits significant CO 2 adsorption capacity in both operations.…”
Section: Resultsmentioning
confidence: 76%
“…This is mainly due to the excellent surface affinity and active pores in the palm shell-based adsorbent. [41][42][43] Overall, it is found that palm shell-based adsorbent exhibits significant CO 2 adsorption capacity in both operations. The adsorption capacity of the adsorbent is determined by varying the moisture content of the adsorbent from 0% to 25% at a regular interval of 5%.…”
Section: Effect Of Adsorbent Quantitymentioning
confidence: 79%
“…Biomass, as the most abundant renewable resource, is currently intensively used for biofuels/chemicals production or can serve as a precursor for the production of porous carbon materials [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Chitosan (CS) is an N -deacetylated product of chitin, which is easily soluble in solvents capable of disrupting hydrogen bonds, e.g., dilute aqueous solutions of organic and mineral acids or some ionic liquids.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the amount of CO 2 in the landfill gas as well as in the coal bed methane needs to be reduced to increase the heat energy efficiency and to reduce global warming when methane is used as an energy resource. 4,5 A commercial technique for separating CO 2 uses an amine absorption method. However, it consumes a lot of energy and causes corrosion of related equipment.…”
Section: Introductionmentioning
confidence: 99%